(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The classification of government grants and assistance received from economic units is one of the important issues for those in charge of external oversight in order to identify the mechanisms used in the use of funds received in grants and aid and conditions or accompanying restrictions have, as varied forms of grants and assistance provided by States and international and regional organizations, there are bilateral grants parties and multilateral grants and has all the characteristics of a particular type, the former features provided by the implementation of the donor itself allocated for projects shall be either the second and implementation by the beneficiary, so that each type Alalaa that Mtaz out and the need to be based on the external control of science and knowledge, and will be in this research dealt with bilateral United Nations, the Organization for privacy parties grants. Accordingly, it has been divided research into four axes, the first axis dealt with the research methodology and the second axis dealt with the definition of government grants and types, mil third axis handled the practical side of the research was chosen as the UN grant to the Ministry of Water Resources and finally addressed the fourth conclusions and recommendations of the axis, which was the most prominent of: - 1- Non-compliance by the donors with the terms of the grant agreement and failure to take seriously the emphasis on its implementation by the recipient. 2- Non-possession of external oversight staff assigned to audit grants implemented by donors sufficient experience in terms of scrutiny of this type of grants thanks to its specificity ranging from verification of approvals and registration in the books and the mechanism of disposition and projects that have been completed from the grant and their conformity with the technical specifications required . 3- We have not touched any role of external oversight in respect of field visits to the work site of the projects in progress or completed from the grant and verify that implementation is in accordance with the grant agreement. 4- The Project Management Office has not been established by the United Nations and its agencies along the lines of the World Bank project management offices. The recommendations were: 1- The beneficiaries and the relevant ministries must ensure that the donor complies with the terms of the grant agreement. 2- Holding training courses in the field of external oversight on the mechanisms to be followed in providing this type of grants. 3- the need to conduct field visits in order to work in terms of security of grants that enable them to achieve their objectives. 4- Emphasize the donor to establish the Office of projects implemented in the Iraqi ministries for the purpose of serious follow - up and reduce costs.